Paranasal sinuses and human identification (Research, Society and Development, 2021)
The characteristics of the paranasal sinuses (maxillary, frontal, sphenoid and ethmoid sinuses) are information of great relevance to Forensic Sciences, as their images can be used for human identification purposes. Due to their particularities, the paranasal sinuses provide valuable information for human identification, reducing the risk of errors during investigation by experts. Such structures are visualized from several imaging exams. This study evaluates the possibilities of human identification through the analysis of the paranasal sinuses, as well as the effectiveness of their analysis in estimating sex, age and ancestry. A comprehensive search was performed in the PubMed, SciELO, LILACS, and Web of Science databases. As inclusion criteria, texts that addressed the subject were selected. Imaging analysis of the frontal, maxillary and sphenoid sinuses is a useful tool for human identification, as well as for estimating sex, age and ancestry; usually provides a high level of accuracy. Regarding the ethmoid sinus, research is indicated to verify its use in human identification, as no publications on this specific subject were found. Additional research must be carried out (especially three-dimensional analysis of the paranasal sinuses), to develop standardized protocols, improving the work of experts, helping justice and society.